Systematic Literature Review: Behavioral Factors Affecting Fraud in Accounting - Maria Dinda Sabrina Sembiring (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to thoroughly examine the various behavioral factors that influence the occurrence of fraud in accounting by using the systematic literature review method. Accounting fraud is an important issue that not only causes financial losses, but also damages the company's reputation and lowers public trust. This study categorizes the behavioral factors that influence the risk of fraud into three main categories, namely individual factors such as the tendency to love money and low morality, organizational factors such as corporate culture that does not uphold ethics, and external factors such as financial pressure. The results show that the love of money and low morality in individuals are the main triggers for fraud, in accordance with the Fraud Triangle and Fraud Diamond which emphasize the role of pressure, opportunity, rationalization, and individual ability. In addition, a corporate culture that allows ethical violations provides greater opportunities for fraud to occur. This research confirms the importance of behavioral accounting for financial decision making because it studies what causes fraud. Improving individual morality, building an ethical organizational culture, and managing external pressures can help prevent fraud. Practically, the results of this study underscore the need to improve individual morale, strengthen internal controls, and ethics training on an ongoing basis as an effort to prevent and early detect fraud in accounting in the future